2015
DOI: 10.1002/jcb.24989
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Annexin A2 in Human Type I Collagen Gene Expression

Abstract: The fibrillar collagen scaffold of the extracellular matrix provides a structural framework for cells in tissues and regulates intercellular communication; its disregulation has been associated with tumour development and progression. Previous work has shown that expression of type I collagen, the most abundant mammalian extracellular matrix protein, is decreased in chemically or virally transformed cells. This negative regulation could be mapped to a proximal COL1A2 promoter element spanning a CME (Collagen M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…This may be explained by the effect of annexin A2 gene deletion on net collagen production as being multifaceted, not just involving extracellular annexin A2. Intracellular annexin A2 is a potential negative posttranscriptional regulator of type I collagen synthesis (36). Although the contribution of FXa to the fibrogenic actions of annexin A2 in vivo were not…”
Section: L778mentioning
confidence: 99%
“…This may be explained by the effect of annexin A2 gene deletion on net collagen production as being multifaceted, not just involving extracellular annexin A2. Intracellular annexin A2 is a potential negative posttranscriptional regulator of type I collagen synthesis (36). Although the contribution of FXa to the fibrogenic actions of annexin A2 in vivo were not…”
Section: L778mentioning
confidence: 99%
“…showed increased expression of LGALS3BP (Table 4) (Chan et al, 2016). In contrast, both decorin (Dcn) and annexin A2 (Anxa2) are negative regulators of collagen 1 assembly/maturation and gene expression, respectively (Mochida et al, 2009;Schäfer et al, 2015). Here, their enhanced expression may be considered a compensatory response to the increased collagen gene expression and deposition.…”
Section: Upregulatedmentioning
confidence: 99%
“…In particular a decrease in the expression of a number of collagen proteins that are associated with cell adhesion was observed that could be associated with the observed up-regulation of annexin A2, which is a regulator of the COL1A2 promoter region (56). A down-regulation of TIMP1, which is an MMP inhibitor, was observed.…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 85%